(3GdJfhjQs - (3ceGd GdOjf GdNdGWis; (3GdNdGWj , eMeO Hf YHGO Hf edc OGO Hf GdMSf Hh OGhO, CHh YHO Gddg,J (B652 (3g` s ((3UGdM Hf bGSe Gdjefi s)
(3ChdgG (B:s
(3HGH GdVe hGdJYLjd s
(3BNQgG (B:s
(3HGH JLgjd GdhOjYI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B182 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B118s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B258 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B567s
Keywords: (3Gdabg GdMfajs